Explaining reallocation's apparent negative contribution to growth - Mitsukuni Nishida; Amil Petrin; Sašo Polanec (The Johns Hopkins University, Department of Economics, 2011)
We explain a puzzle from two recent meta-analyses that cover 25 countries and claim to show that inputs systematically move from higher-value to lower-value activities despite strong aggregate labor productivity growth (ALP). These papers use variants of the Baily, Hulten and Campbell (1992) decomposition of ALP to show that the reallocation covariance term is negative in all but two countries and the reallocation between term is negative in nine countries and weakly positive in most others. We decompose ALP using three micro-level data sets from Chile, Colombia, and Slovenia and show the same puzzle holds. We show that the ALP between term can be decomposed into a term related to reallocation and a term related to the change in the total number of .ms, the latter of which often works to reduce the total between term in our data. We also show these ALP patterns can arise because of heterogeneity in labor and capital, unobserved output prices, or capacity utilization, but controlling for them only marginally helps to explain away the ALP reallocation puzzles in our micro-level data sets. We show that there is no puzzle when one decomposes aggregate productivity growth in the terms of National Accounts, as inputs in the aggregate move from low to high value activities in 36 of our 39 country-year observations. We conclude that there is a fundamental difference in re-allocation measured by the ALP decomposition and that measured by the decomposition of National Accounts growth.
Keywords: 330; Arbeitsproduktivität; Wirtschaftswachstum; Arbeit; Allokation; Schätzung; Welt